Synergistic effect of polyherbal formulations on DPPH radical scavenging activity - Abdul Rahim, Nur Fazira; Muhammad, Norhayati; Abdullah, Norazlin; A. Talip, Balkis; Dusuki, Nur Jihan Shahirah (UTHM, 2018)
Plant extracts contains huge number of chemical compounds that may give interaction effect which could affect the antioxidant properties especially when mixed together. Therefore, in this present study, the synergistic effect towards 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging activity presence in aqueous extract of herbal leaves of Strobilanthes crispus (Pecah beling), Phyllanthus niruri (Dukung anak), Orthosiphon aristatus (Misai kucing) and Stevia rebudiana has been evaluated. Synergy is the interaction of two or more extracts to produce a combined effect greater than the totality of their individual effects. There were 22 formulations consisting various proportions of the extracts designated using the commercial statistical software package which is Design Expert 6.0.4. The in-vitro antioxidant study of the extracts and their different combinations were conducted by DPPH radical scavenging activity. The results suggest that O. aristatus has higher potential of antioxidant properties. Synergistic effect was exhibited in the majority of all combinations as well as the combination of the four plant extracts. The highest synergistic effect indicated in the fifth formulation (S. crispus and P. niruri). However, the sixth formulation (S. crispus and S. rebudiana) showed the lowest synergistic effect. In conclusion, the present study justifies these polyherbal formulations have promising antioxidant properties in term of DPPH radical scavenging activity and validates their synergistic effect by having an improved activity in most of the formulations. Thus, it is sensible to mix the studied polyherbal formulations as food supplements or food ingredients in the future.